Acute zonal occult outer retinopathy complex disease: Lessons learned about choroid, photoreceptors, and retinal function. Issue 2 (March 2021) - Pellegrini, Francesco; Cirone, Daniele; De Simone, Luca; Marullo, Michele; Cimino, Luca
Purpose: Retinal photoreceptors layer integrity is considered essential to visual function. We report a case of acute zonal occult outer retinopathy (AZOOR) complex disease (namely AIBSE: acute idiopathic blind spot enlargement) in which apparently a full anatomic regeneration is not needed for a complete functional recovery. Methods: Case report with multimodal imaging. Reports: Visual field recovery in the presence of photoreceptors layer disruption studied by means of Optical Coherence Tomography. Choroid and photoreceptors layer thickness thinned progressively during recovery. Conclusion: This case suggests that anatomical retinal integrity as shown by OCT does not always correspond to visual function. Our case highlights that a complete visual recovery can occur even when structural abnormalities are still observable.